Evaluation of relationship between hematocrit and lipid profile in adults - Gabriel P. R. Lopes; Marcos A. G. Munhoz; Leila Antonangelo (Sociedade Brasileira de Patologia Clínica, 2018)
ABSTRACT Introduction and objective: This study was carried out to analyze the relationship between hematocrit and lipid profile in adults. Material and method: A sample composed of complete blood counts and lipid profiles from the database of Hospital das Clínicas da Universidade de São Paulo (HCUSP), São Paulo, Brazil, was used in the analysis. Hematocrit was organized in five groups that were compared with total cholesterol (TC), low-density-lipoprotein cholesterol (LDL-C), non-high-density-lipoprotein cholesterol (NHDL-C) and high-density-lipoprotein cholesterol (HDL-C) by means of chi-squared and Kruskal-Wallis tests. Results: Both tests showed a relevant correlation between hematocrit and lipid profile, considering a p-value < 0.05. Moreover, descriptive statistics revealed that the higher the hematocrit, the higher the proportion of people without recommended levels of each type of cholesterol, such TC, LDL-C, and NHDL-C. Just HDL-C showed an inverse association compared to the other variables, with an increased proportion of recommended levels along with rising of hematocrit. Conclusion: The relationship between hematocrit and lipid profile in all aspects of this study was more evident in women; nevertheless, the higher proportion of not recommended levels of HDL-C was shown in men. The reverse cholesterol transport probably plays an important role in the increase of cholesterol levels in blood in the presence of high hematocrit, by interaction of HDL-C and erythrocytes. Thus, further studies are necessary to elucidate these findings and to describe more aspects of the reverse cholesterol transport and its relationship with hematocrit and lipid profile.